2020
DOI: 10.1098/rspb.2020.1001
|View full text |Cite
|
Sign up to set email alerts
|

Rhythms during the polar night: evidence of clock-gene oscillations in the Arctic scallopChlamys islandica

Abstract: Arctic regions are highly impacted by climate change and are characterized by drastic seasonal changes in light intensity and duration with extended periods of permanent light or darkness. Organisms use cyclic variations in light to synchronize daily and seasonal biological rhythms to anticipate cyclic variations in the environment, to control phenology and to maintain fitness. In this study, we investigated the diel biological rhythms of the Arctic scallop, Chlamys islandica , during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Mat et al [22] suggested that this weak endogenous oscillator would certainly confer plasticity on this species, partly explaining its adaptability to various environments. Indications of such a mechanism also have been found in C. islandica, which maintains its gaping behavior during the polar night [32,62].…”
Section: Plos Onementioning
confidence: 62%
See 1 more Smart Citation
“…Mat et al [22] suggested that this weak endogenous oscillator would certainly confer plasticity on this species, partly explaining its adaptability to various environments. Indications of such a mechanism also have been found in C. islandica, which maintains its gaping behavior during the polar night [32,62].…”
Section: Plos Onementioning
confidence: 62%
“…Indications of such a mechanism also have been found in C . islandica , which maintains its gaping behavior during the polar night [ 32 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the putative core circadian clock genes period, timeless, and cry1 (a dCry/L-Cry ortholog) exhibited approximate tidal rhythms in field samples (Mat et al 2020), suggesting the plasticity of the ∼24-h oscillator. Similarly, putative core circadian clock genes showed daily and/or tidal oscillations in the Iceland scallop (Chlamys islandica) during equinox and polar night (Perrigault et al 2020).…”
Section: Rhythms In the Deep Seamentioning
confidence: 97%
“…The outputs of this conserved structure are circadian (Dunlap, 1999). Homologous clock genes (clock and bmal as activators and cryptochrome 1 and 2, period and timeless as repressors) have been described for bivalves, such as the oyster Magallana gigas (Perrigault and Tran, 2017), the mussels M. edulis (Chapman et al, 2020) and M. californianus (Connor and Gracey, 2011), the scallops Argopecten irradians (Pairett and Serb, 2013) and Chlamys islandica (Perrigault et al, 2020) and even in the deep-sea [i.e., Bathymodiolus azoricus (Mat et al, 2020)]. The main periods associated with biological clocks in bivalves are daily and tidal, but others with lower (several days to a year) or higher frequencies (hours to minutes) have also been reported (Figure 6B).…”
Section: Biological Clocks In Bivalvesmentioning
confidence: 99%